Mechanism of drug resistance of BVDV induced by F224S mutation in RdRp: A case study of VP32947. (August 2022) - He, Dian; Li, Xuedong; Wang, Songsong; Wang, Chengzhao; Liu, Xingang; Zhang, Yang; Cui, Yan; Yu, Sijiu
Abstract: Bovine viral diarrhea virus (BVDV) is an enveloped virus with an RNA genome, causing serious economic losses to the areas dominated by livestock industry. Currently, although several compounds with biological activities of inhibiting virus replication have been reported, amino acid mutations (especially F224S mutation) frequently occurring in the RNA-dependent RNA polymerase (RdRp) have greatly reduce their value of further research. In this study, we introduced an effective and rapid in silico strategy to explore the differences in the binding modes of VP32947 between the wild/mutant-type RdRp at the molecular level, and further explained the main reasons for the variations in the inhibitory activities of VP32947 against the two types of enzymes. Firstly, the binding site of VP32947 in the finger domain was determined based on the previously reported experimental data, and the initial conformation of VP32947 in the wild RdRp was constructed using molecular docking. Then, the mutant research system was obtained directly by artificial mutation strategy. Afterwards, the built research systems were subjected to microsecond-timescale molecular dynamic simulation, and the conformational and energic profile analyses were performed according to the simulation trajectories. It was found that after 1 μs simulation, VP32947 in the mutant system was transferred to the left side of Loop α, and its interactions with the residues in the loop region were weakened. However, VP32947 in the wild system remained at the right side of Loop α, and could have a good fit with the sub-pocket formed by F224, I261, P262, N264, S532, which was conducive to maintaining its stable binding conformation in the wild RdRp. The illustration of the difference in the binding mechanisms of VP32947 in the wild/mutant RdRp would provide a theoretical basis for the rational design of innovative inhibitors based on the enzyme. Graphical Abstract: ga1 Highlights: BVDV, as an enveloped virus with an RNA genome, has led to serious economic losses. Resistance caused by F224S mutation severely limited further drug development. Computational approaches illustrated the differences in the binding mechanisms of VP32947 in wild/mutant RdRp. The key residues contributing to VP32947's binding in the wild receptor were identified.